HDR brachytherapy as monotherapy for prostate cancer: A systematic review with meta-analysis - Viani, Gustavo Arruda (2021)
Purpose: The effectiveness and safety of high dose brachytherapy as monotherapy (HDR-BRT-M) in prostate cancer is limited to retrospective studies. We performed a meta-analysis to summarize existing data and identify trends in biochemical recurrence-free survival (bRFS) and toxicity after HDR-BRT-M in patients with prostate cancer. Methods and Materials: Retrospective, prospective, or randomized clinical trials were identified on electronical databases through June 2020. We followed the PRISMA and MOOSE guidelines. A meta-regression analysis was performed to assess if there is a relationship between moderator variables and bRFS. A p-value < 0.05 was considered significant. Results: Fourteen studies with a total of 3534 patients treated were included. The cumulative size of the bRFS at 5 years was 0.92 (95% confidence interval (CI) 0.48–0.61). The five-year bRFS for low, intermediate, and high risk was 97.5% (95% CI 96–98%), 93.5% (95% CI 91–96%), and 91% (95% CI 88–93%), respectively. The total biological effective dose (BED) (p = 0.02), the BED per fraction (p = 0.001), androgen deprivation therapy usage (p = 0.04), and the number of fractions of HDR-BRT-M (p = 0.024) were significantly associated with bRFS rate. The rate of late Grade 2/3 or > genitourinary and gastrointestinal toxicity was 22.4% (95% CI 9–35,2%)/1.4% (95% CI 0.8–2.1%) and 2.7% (95% CI 0–6.8%) and 0.2% (95% CI 0.1%–0.4%), respectively. Conclusions: HDR-BRT-M is safe with excellent rates of bRFS for all risk groups. The total BED, the BED per fraction, and number of fractions were the key factors associated with the biochemical control. These data can be useful to choose the size and number of BRT fractionation.